Systemic Arterial Hypertension in people living with HIV/AIDS: integrative review - Maria Amanda Correia Lima; Gilmara Holanda da Cunha; Marli Teresinha Gimeniz Galvão; Ryvanne Paulino Rocha; Kátia Barbosa Franco; Marina Soares Monteiro Fontenele
ABSTRACT Objective: To analyze scientific productions about the relationship between HIV and Systemic Arterial Hypertension (SAH) in people living with HIV/AIDS (PLWHA). Method: Integrative literature review in six databases, held in March 2016. "AIDS" and "hypertension" were the keywords used in Portuguese, English and Spanish languages. We found 248 articles and selected 17. The categories formulated were "prevalence of SAH in PLWHA," "risk factors for SAH in PLWHA" and "adverse events of antiretroviral therapy (ART) that contribute to HAS." Results: There is no consensus whether HIV and ART influence the SAH development, but there are several risk factors for SAH among PLWHA. It was observed that protease inhibitors medicines influence SAH the most. Conclusion: Guidelines for SAH prevention must be performed in all individuals, however, in PLWHA, they must focus on characteristic risk factors of this population.